2006
DOI: 10.1175/mwr3195.1
|View full text |Cite
|
Sign up to set email alerts
|

The Sensitivity of Simulated Convective Storms to Variations in Prescribed Single-Moment Microphysics Parameters that Describe Particle Distributions, Sizes, and Numbers

Abstract: The sensitivity of cloud-scale simulations of deep convection to variations in prescribed microphysics parameters is studied, using the single-moment scheme in the Regional Atmospheric Modeling System (RAMS) model. Realistic changes were made to the shape parameters in the gamma distributions of the diameters of precipitating hydrometeors and of cloud droplets, in the number concentration of cloud droplets, and in the mean size of the hail and graupel. Simulations were performed with two initial soundings that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 63 publications
3
56
0
Order By: Relevance
“…PW impacts the amount of condensate present within the updraft and thus the vertical velocity. The three parameter space used in this study is a subset of higher dimensional parameter spaces utilized by prior numerical modeling studies of thunderstorm morphology and evolution (Cohen, 2000;McCaul Jr. and Weissman, 2001;McCaul Jr. et al, 2005;Cohen and McCaul Jr., 2006;Kirkpatrick et al, 2007;Kirkpatrick et al, 2011). Note that these studies do show that CAPE, SHEAR and PW modulate cloud mass flux, cloud entrainment and hydrometeor mass distribution in thunderstorms and all of these processes are important to wet deposition removal of atmospheric mercury.…”
Section: Meteorological Datamentioning
confidence: 99%
“…PW impacts the amount of condensate present within the updraft and thus the vertical velocity. The three parameter space used in this study is a subset of higher dimensional parameter spaces utilized by prior numerical modeling studies of thunderstorm morphology and evolution (Cohen, 2000;McCaul Jr. and Weissman, 2001;McCaul Jr. et al, 2005;Cohen and McCaul Jr., 2006;Kirkpatrick et al, 2007;Kirkpatrick et al, 2011). Note that these studies do show that CAPE, SHEAR and PW modulate cloud mass flux, cloud entrainment and hydrometeor mass distribution in thunderstorms and all of these processes are important to wet deposition removal of atmospheric mercury.…”
Section: Meteorological Datamentioning
confidence: 99%
“…When only considering condensation, theoretical arguments and parcel modeling have shown that the distribution narrows less (shape parameter increases less) for distributions with initially higher cloud droplet or aerosol concentrations (Yum and Hudson 2005;Liu et al 2006;Peng et al 2007;Pinsky et al 2014). In turn, the shape of the droplet distribution can influence the rate at which these processes act (e.g., Milbrandt and Yau 2005a;Cohen and McCaul 2006). For example, a higher shape parameter (narrower distribution) is expected to result in slower collection of cloud water by rain (Cohen and McCaul 2006) and reduced size sorting for precipitating hydrometeors (Milbrandt and Yau 2005a).…”
Section: Introductionmentioning
confidence: 99%
“…For the purpose of this study, single-moment bulk microphysics parameterization scheme is used as in other sensitivity studies of the similar type (Van den Heever and Cotton, 2004;Cohen and McCaul, 2006). The model microphysics represents cloud water, rain and three classes of ice (cloud ice, snow and hail).…”
Section: Model Descriptionmentioning
confidence: 99%
“…The improvement of model microphysics is essential because convective precipitation is very sensitive to the uncertainties in cloud microphysics (Gilmore et al, 2004a,b;Spiridonov andĆurić, 2005). The choice of a hydrometeor size distribution is critical for the cloud model outputs (Ćurić et al, 1998;Cohen and McCaul, 2006). There are studies that use the meteorological models to simulate the convective precipitation over a large area as well as to compare the modeled and observed datasets (e.g.…”
Section: Introductionmentioning
confidence: 99%